If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + y + 130 = 3x + y + 160 Reorder the terms: 130 + 2x + y = 3x + y + 160 Reorder the terms: 130 + 2x + y = 160 + 3x + y Add '-1y' to each side of the equation. 130 + 2x + y + -1y = 160 + 3x + y + -1y Combine like terms: y + -1y = 0 130 + 2x + 0 = 160 + 3x + y + -1y 130 + 2x = 160 + 3x + y + -1y Combine like terms: y + -1y = 0 130 + 2x = 160 + 3x + 0 130 + 2x = 160 + 3x Solving 130 + 2x = 160 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 130 + 2x + -3x = 160 + 3x + -3x Combine like terms: 2x + -3x = -1x 130 + -1x = 160 + 3x + -3x Combine like terms: 3x + -3x = 0 130 + -1x = 160 + 0 130 + -1x = 160 Add '-130' to each side of the equation. 130 + -130 + -1x = 160 + -130 Combine like terms: 130 + -130 = 0 0 + -1x = 160 + -130 -1x = 160 + -130 Combine like terms: 160 + -130 = 30 -1x = 30 Divide each side by '-1'. x = -30 Simplifying x = -30
| 6x+9=-2x+105 | | 6x+9=-2+105 | | f(81)=74 | | 6y-8-2y+3=0 | | 6n+1=.5 | | (x+y+z)(x+y)-(x-y-z)(x-y)= | | 4+4q=9+3q | | 7*4p-5*3r+3*3q-5*5r+4*5q-10q= | | 3x/4-12=3 | | 2w+1+w=18 | | 0.36(24)+0.04=0.12(6+x) | | 11*11/12-3 | | 8x+4=-2(6x-1) | | y-5=2/4(x-2) | | 7x+5(2+x)=-2 | | (1/3)8 | | 3-4x=2x+25 | | 6x+3=34x+7 | | 23-[3+9y-3(y+3)]=-3(4y-6)-[8(y-1)-10y+13] | | 3(2x+6)+12=-15 | | 5(1-3m)=30-(4m+7) | | 3x-4.9=0 | | x^2-3ax-10a^2=0 | | 7y+6=2y-9 | | 12(3x+4)-5(2x-5)=6x-67 | | 13r+16=5t | | -5-10b=15-11b | | (0.2x+3)(0.2x-3)=0 | | 4[x+2(5-x)]=3x+1 | | 15+11h=10h | | 12y-6+2y+8=12solve | | 5x-3x=7 |